Chemoenzymatic Site‐Specific Reversible Immobilization and Labeling of Proteins from Crude Cellular Extract Without Prior Purification Using Oxime and Hydrazine Ligation. Issue 2 (June 2013) - Mahmoodi, Mohammad M.; Rashidian, Mohammad; Dozier, Jonathan K.; Distefano, Mark D.
Abstract: In a facile and potentially general method for protein modification at the C‐terminus, aldehyde‐modified proteins, obtained from enzymatic protein prenylation, react rapidly with hydrazide and aminooxy surfaces and fluorophores at neutral pH and in micromolar concentration ranges of reagents. This strategy was used for fluorescent labeling of eGFP‐CVIA, as a model protein, with aminooxy and hydrazide fluorophores or PEGs, and immobilization onto and subsequent release of the protein from hydrazide‐functionalized agarose beads using hydrazone‐oxime exchange. This method is described in detail here and provides site‐specifically PEGylated or fluorescently labeled proteins starting from crude cellular extract in three steps: prenylation, capture, and release. Curr. Protoc. Chem. Biol. 5:89‐109 © 2013 by John Wiley & Sons, Inc.